Periodontitis and bone mineral density among pre and post menopausal women: A comparative study - Suresh Snophia; Kumar T.S.S; Saraswathy P; Pani Shankar K (Wolters Kluwer Medknow Publications, 2010)
Aim: The aim of the study was to assess the relationship between bone mineral density and periodontitis in premenopausal and postmenopausal women. Materials and Methods: Twenty women between the age group of 45-55 years were selected for this study. Ten premenopausal women with healthy periodontium constituted the control group and 10 postmenopausal women with ≥2mm of clinical attachment loss in> 30% of sites constituted the study group. All patients were assessed for plaque index, probing depth and clinical attachment loss. Radiographs (six IOPA and two posterior bitewing) were taken and assessed for interproximal alveolar bone loss. The patients were scanned to assess the bone mineral density of lumbar spine (L2) and femur using dual energy X-ray absorptiometry (DEXA). Results: The bone mineral densities of lumbar spine (L2) and femur were significantly lower in the study group than the control group. Osteopenia of the lumbar spine and femur was observed in 60% whereas osteoporosis of lumbar spine was observed in 30% of cases in study group. Conclusion: Increased proportion of osteopenia and osteoporosis cases of lumbar spine and femur in postmenopausal women with periodontitis suggests that there is association between bone mineral density and periodontitis.